Lithium ion battery and preparation method and application thereof

By using elemental boron as the positive electrode lithium supplement agent in lithium-ion batteries, the charge balance is formed with the lithium ions embedded in the negative electrode through oxidation reaction, the problems of low cycle life and energy density of lithium-ion batteries are solved, and the gas production is not increased The cycle performance and energy density are significantly improved in the case.

CN119315087AActive Publication Date: 2025-01-14ENVISION DYNAMICS TECH (JIANGSU) CO LTD +1

Patent Information

Application Number
CN202411420215.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-01-14
Estimated Expiration
2044-10-11

AI Technical Summary

Technical Problem

The battery life and cycle life of lithium-ion batteries cannot meet the needs, especially the lithium iron phosphate system has low energy density and poor cycle life, and the cycle life of the high-energy density positive and negative electrode system is not good, and the commonly used lithium supplement agents release oxygen during charging, resulting in Gas production increases and circulation becomes worse.

Method used

The use of elemental boron as the positive electrode lithium supplement agent, and the charge balance is formed with the lithium ions embedded in the negative electrode through the oxidation reaction, improves the film formation quality of the positive electrode electrolyte interface film, reduces the DC impedance, and is generated in situ on the surface of the positive electrode active material through the reduction method. Improve contact density.

Benefits of technology

It significantly improves the circulation performance and energy density of lithium-ion batteries without deteriorating gas production, extends the cycle life, enhances the positive electrode lithium supplement effect, and optimizes battery performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005082379500000161
    Figure BDA0005082379500000161
  • Figure BDA0005082379500000171
    Figure BDA0005082379500000171
  • Figure BDA0005082379500000181
    Figure BDA0005082379500000181
Patent Text Reader

Abstract

The invention provides a lithium ion battery and a preparation method and application thereof, the lithium ion battery comprises: a positive pole piece, the positive pole piece comprises a lithium supplement agent, the lithium supplement agent comprises elemental boron; a negative pole piece; the diaphragm is arranged between the positive pole piece and the negative pole piece; and the electrolyte is filled among the positive pole piece, the negative pole piece and the diaphragm. According to the lithium ion battery as well as the preparation method and the application thereof provided by the invention, a relatively high positive electrode lithium supplementing effect can be achieved in various battery systems under the condition that gas production is not deteriorated, and the cycle performance of the lithium ion battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium ion battery and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries are the core components driving the electrification transformation of the automotive industry. However, the battery life and cycle life of lithium-ion batteries cannot meet the demand. Therefore, under the condition of controllable costs, improving the energy density and cycle life of lithium-ion batteries will be the development direction of lithium-ion batteries for electric vehicles for some time. Among them, the energy density of lithium iron phosphate systems with low prices and excellent cycle life is low, while positive and negative electrode chemical systems with high energy density, such as high nickel or high silicon systems, face the problem of poor cycle life.

[0003] During the first cycle of lithium-ion batteries, a solid electrolyte interphase (SEI) is formed on the surface of the negative electrode, resulting in irreversible lithium loss, thereby reducing the energy density of lithium-ion batteries. By introducing positive electrode lithium replenishment technology containing lithium compound additives into the positive electrode of lithium batteries, the lithium replenisher undergoes irreversible decomposition during the charging process, releasing active lithium, thereby achieving a replenishment effect. However, the commonly used positive electrode lithium replenishers such as lithium-rich nickel oxide (Li2NiO2, LNO) and lithium-rich iron oxide (Li5FeO4, LFO) have obvious oxygen release problems during the first charging process, resulting in increased gas production and poor cycle performance. Therefore, the LNO or LFO doping levels commonly used in the industry are less than 1wt%, and the benefits brought are limited. Summary of the invention

[0004] The present invention proposes a lithium-ion battery and its preparation method and application, which can play a high role in positive electrode lithium replenishment in various battery systems without deteriorating gas production, and improve the cycle performance of lithium-ion batteries. The product of the lithium replenisher after oxidation can improve the film quality of the positive electrode electrolyte interface film and reduce the DC impedance.

[0005] In order to solve the above technical problems, the present invention provides a lithium ion battery, comprising at least:

[0006] A positive electrode plate, wherein the positive electrode plate includes a lithium supplement, and the lithium supplement includes elemental boron;

[0007] Negative electrode;

[0008] A separator, disposed between the positive electrode sheet and the negative electrode sheet; and

[0009] The electrolyte is filled between the positive electrode sheet, the negative electrode sheet and the separator.

[0010] In one embodiment of the present invention, the positive electrode plate includes a positive current collector and a positive active material layer disposed at least on one side of the positive current collector, and the content of the lithium supplement in the positive active material layer is 0.08wt% to 2wt%.

[0011] In one embodiment of the present invention, the positive electrode active material layer includes a positive electrode active material, and the positive electrode active material is selected from at least one of lithium iron phosphate and lithium manganese iron phosphate.

[0012] In one embodiment of the present invention, the positive electrode active material layer comprises a positive electrode active material, and the positive electrode active material is selected from LiNi x Co y Mn 1-x-y O2, where 0.65≤x<1.0, 0≤y<0.5.

[0013] In one embodiment of the present invention, the negative electrode plate includes a negative electrode current collector and a negative electrode active material layer disposed at least on one side of the negative electrode current collector, the negative electrode active material layer includes a negative electrode active material, and the negative electrode active material is selected from at least one of graphite, silicon oxide material or silicon carbon material.

[0014] The present invention also provides a method for preparing a lithium ion battery, comprising at least the following steps:

[0015] Mixing a lithium supplement agent into the positive electrode active material to obtain a mixed active powder;

[0016] The mixed active powder is prepared into positive electrode slurry;

[0017] The positive electrode slurry is coated on the positive electrode current collector, and then dried and cold pressed to obtain a positive electrode sheet;

[0018] preparing negative electrode active materials into negative electrode slurry;

[0019] The negative electrode slurry is coated on the surface of the negative electrode current collector, and then dried and cold pressed to obtain a negative electrode sheet; and

[0020] The lithium-ion battery is obtained by assembling the positive electrode sheet, the negative electrode sheet, the electrolyte and the separator.

[0021] In one embodiment of the present invention, the lithium supplement agent and the positive electrode active material are uniformly mixed by ball milling.

[0022] In one embodiment of the present invention, the powder particle size of the lithium supplement agent is 10nm to 500nm.

[0023] In one embodiment of the present invention, the blended active powder is obtained by the following method:

[0024] Add the positive electrode active material to the ice water or ice N,N-dimethylacetamide solvent containing ammonium fluoride, first dissolve the boric acid according to the amount of the lithium supplement, stir and mix evenly, then gradually add dimethylamine borane or lithium borohydride dropwise;

[0025] After the dropwise addition is completed, the mixture is reacted for a first preset time, filtered and washed to obtain an intermediate product;

[0026] The intermediate product is calcined at a preset temperature and oxygen environment for a second preset time.

[0027] The present invention also provides an electronic device, comprising the lithium-ion battery described above.

[0028] In summary, the present invention proposes a lithium ion battery and its preparation method and application. By selecting elemental boron as a positive electrode lithium supplement, during charging, an oxidation reaction occurs to contribute a large number of charges, and after oxidation, it will be positively charged, which can form a charge balance with the lithium ions embedded in the negative electrode, and will not cause the solution ion charge to be non-conserved because it does not contribute lithium ions, and can achieve the lithium supplement effect. At the same time, elemental boron has a large specific capacity and a strong ability to fill the irreversible capacity of the negative electrode, which can play a high positive electrode lithium supplement effect. The product after oxidation of the lithium supplement can improve the film quality of the positive electrode electrolyte interface film and reduce the DC impedance. Through the reduction method, elemental boron is in situ generated on the surface of the positive electrode active material, and its contact with the positive electrode active material is closer. Compared with the ball milling method, it is easier to exert the capacity, and the performance improvement of the lithium ion battery is better. When elemental boron is used as a positive electrode lithium supplement, it can be applied to a variety of battery systems, and can improve the cycle performance of lithium ion batteries without deteriorating gas production. DETAILED DESCRIPTION

[0029] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0030] It should be understood that the present invention can be implemented in different forms and should not be construed as being limited to the embodiments set forth herein. On the contrary, providing these embodiments will make disclosure thorough and complete, and will fully convey the scope of the present invention to those skilled in the art. If not otherwise specified, the "%" and "parts" shown in the following examples refer to "mass %" and "mass parts" respectively.

[0031] The technical solution of the present invention will be further described in detail below in conjunction with several embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative work belong to the scope of protection of the present invention.

[0032] The present invention provides a lithium-ion battery, which includes a positive electrode sheet, a negative electrode sheet, a separator, and an electrolyte. The separator is located between the positive electrode sheet and the negative electrode sheet, and the electrolyte is filled between the positive electrode sheet, the negative electrode sheet, and the separator. Among them, the positive electrode sheet includes a lithium supplement agent, and the lithium supplement agent includes elemental boron. The present invention does not limit the type and shape of the lithium-ion battery. In one embodiment of the present invention, the lithium-ion battery is, for example, a secondary battery, and the secondary battery is, for example, a soft-pack battery, a hard-shell battery, or a cylindrical battery, etc. In this embodiment, for example, a soft-pack secondary battery is taken as an example for elaboration.

[0033] In one embodiment of the present invention, the positive electrode sheet includes a positive electrode current collector and at least a positive electrode active material layer provided on one side of the positive electrode current collector. The positive electrode current collector is, for example, a foil formed after surface treatment of nickel, titanium, aluminum, nickel, silver, stainless steel, or carbon, etc. The surface of the positive electrode current collector is smooth, and fine纹路 can also be formed on the surface of the positive electrode current collector to improve the adhesion between the positive electrode active material and the positive electrode current collector. In addition to the foil, the positive electrode current collector can also be used in any one or a combination of multiple forms such as film-like, net-like, porous, foam, or non-woven fabric.

[0034] In one embodiment of the present invention, the positive electrode active material layer includes a positive electrode active material, a lithium supplement agent, a binder, and a conductive agent, etc. The positive electrode active material is, for example, selected from at least one of lithium iron phosphate (LiFePO4, LFP) or lithium manganese iron phosphate (LiFe a Mn 1-a PO4, 0.1 < a ≤ 0.5, LMFP), etc., to improve the energy density of the long-cycle lithium-ion battery. The positive electrode active material can also be a ternary high-nickel material (NCM), and the general formula of the ternary high-nickel material is, for example, LiNi x Co y Mn 1-x-y O2, where 0.65 ≤ x < 1.0, 0 ≤ y < 0.5, to extend the cycle life of the high-energy-density lithium-ion battery.

[0035] In one embodiment of the present invention, when the lithium-ion battery is charged, the positive electrode active material releases lithium and electrons at the same time, and the electrons undergo a reduction reaction at the negative electrode through an external circuit. If an equal amount of lithium is embedded in the negative electrode, then this part of lithium (lithium carbide) can reversibly release lithium ions and electrons again during discharge, contributing to the reversible capacity. In this state, there is no loss of active lithium. The loss of active lithium at the negative electrode comes from the oxidation reaction at the positive electrode, and the released charge is not completely converted into a lithium ion embedding reaction at the negative electrode, but a side reaction of electrolyte decomposition occurs. Therefore, this part of the capacity is of course irreversible, resulting in active lithium loss, that is, the lithium equivalent extracted from the positive electrode is not converted into a capacity that can be reversibly discharged at the negative electrode. Therefore, considering the existence of active lithium loss, the lithium ion embedding-extraction equivalent of the positive and negative electrodes during charging is not necessarily equal, and the negative electrode does not need lithium ions to migrate from the positive electrode to undergo an embedding reaction. All lithium ion exchanges are carried out with the electrolyte near the positive and negative electrodes. What is truly conserved in this process is the amount of charge that reacts at the positive and negative electrodes. Therefore, during the charging process, the substances in the positive electrode that can be oxidized and contribute charge can fill the capacity of the negative electrode where lithium ions are not embedded.

[0036] In one embodiment of the present invention, the lithium supplement agent includes, for example, elemental boron (B), etc. After experiments, elemental boron can achieve a charging capacity of 1500mAh / g, the reversible capacity is negligible, and the charging voltage is 4.5V. And the relative atomic mass of elemental boron is 10.81g / mol, in order to improve the energy density and cycle performance of the battery, the highest oxidation number is III, so its theoretical capacity is an astonishing 7.44Ah / g. When elemental boron is selected as the positive electrode lithium supplement agent, oxidation can occur during charging, and the number of charges contributed is large. After oxidation, elemental boron will be positively charged, so it can form a charge balance with the lithium ions embedded in the negative electrode, and will not cause the solution ion charge to be non-conserved because it does not contribute lithium ions, and can achieve the lithium supplement effect. At the same time, the specific capacity of elemental boron is large, and the ability to fill the irreversible capacity of the negative electrode is strong, which can play a higher positive electrode lithium supplement effect. In addition, in lithium-ion batteries, the oxidation product of elemental boron may be LiBF4, which basically has no ability to reversibly react back to boron. At the same time, LiBF4 is also an additive that can improve the film quality of the cathode electrolyte interface (CEI) and reduce the direct current resistance (DCR).

[0037] In one embodiment of the present invention, the content of the lithium supplement in the positive electrode active material layer is, for example, 0.08wt% to 2wt%. As the content of the lithium supplement increases, the battery cycle life can be improved without deteriorating the gas production performance. When the amount of elemental boron added is small, the lithium supplement effect is not obvious, and the improvement of the performance of the lithium-ion battery is not obvious. When the amount of elemental boron added is large, the conductivity of elemental boron is poor, resulting in a decrease in the performance of the lithium-ion battery.

[0038] In one embodiment of the present invention, the adhesive is selected from any one or more of polyvinylidene fluoride (PVDF), polyamide (PA), polyacrylonitrile (PAN), polyacrylate, polyvinylether, polymethylmethacrylate (PMMA), ethylene-propylene-diene terpolymer (EPDM), polyhexafluoropropylene or styrene butadiene rubber (SBR). The conductive agent is selected from any one or more of conductive carbon black (SP), acetylene black, carbon nanotubes and graphene.

[0039] In one embodiment of the present invention, when preparing the positive electrode plate, the lithium supplement agent is first mixed into the positive electrode active material to obtain a mixed active powder. The mixed active powder is obtained, for example, by ball milling. According to the ratio set by the lithium supplement agent, the positive electrode active material and the nano-elemental boron are weighed and blended, and ball milling is performed under the protection of an inert gas. In this embodiment, the size of the grinding ball is, for example, 20 mm and 15 mm, and the number of 20 mm and 15 mm grinding balls is equal, the powder particle size of the elemental boron is, for example, 10 nm to 500 nm, the ball-to-material ratio is, for example, 1:1, the ball milling speed is, for example, 400 rpm / min to 600 rpm / min, the ball milling time is, for example, 10 h to 15 h, and the inert gas is, for example, argon, etc., so that the positive electrode active material and the nano-elemental boron are evenly mixed.

[0040] In another embodiment of the present invention, the blended active powder is obtained, for example, by a reduction method. Specifically, the positive electrode active material is added to ice water or ice N,N-dimethylacetamide solvent containing ammonium fluoride. According to the amount of lithium supplement, boric acid (H3BO3) is first dissolved as an oxidant, and dimethylamine borane (DMAB) or lithium borohydride (LiBH4) is gradually added as a reducing agent after stirring and mixing. After the addition is completed, the reaction is carried out for a first preset time, and then filtered and washed to obtain an intermediate product, and then the intermediate product is calcined for a second preset time at a preset temperature and oxygen environment. Among them, the intermediate product is washed with deionized water, for example, the first preset time is 3h to 3.5h, the preset temperature is 730℃ to 780℃, and the second preset time is 1h to 2h. When the blended active powder is obtained by the reduction method, the elemental boron is generated in situ on the surface of the positive electrode active material, and its contact with the positive electrode active material is closer, and it is easier to exert capacity.

[0041] In one embodiment of the present invention, the positive electrode current collector is, for example, selected from aluminum foil, and the thickness is, for example, 8 μm to 16 μm. After the active powder, binder and conductive agent are mixed, for example, in a mass ratio of 95 to 98:1 to 2:1 to 3, an organic solvent is added and stirred until the system is uniform to obtain a positive electrode slurry. Among them, the organic solvent is, for example, selected from N-methylpyrrolidone (NMP). The positive electrode slurry is evenly coated on the aluminum foil, and after drying at room temperature, the aluminum foil is placed in a vacuum drying oven, for example, and dried at 120°C for 1h to 10h, and then the dried aluminum foil is cold pressed and cut, etc. to make a positive electrode sheet.

[0042] In one embodiment of the present invention, the negative electrode sheet includes, for example, a negative electrode current collector and a negative electrode active material layer disposed at least on one side of the negative electrode current collector, and the negative electrode active material layer includes a negative electrode active material, a binder, a conductive agent, and a thickener. The negative electrode current collector is selected from, for example, a copper foil current collector, a composite copper foil current collector, a carbon current collector, a foam copper current collector, or a stainless steel current collector. The negative electrode active material is selected from, for example, at least one selected from graphite, silicon oxygen material, or silicon carbon material, and the binder is selected from, for example, polyvinylidene fluoride, polyamide, polypropylene, polyacrylate, polyvinyl ether, polymethyl methacrylate, polyacrylic acid (Polyacrylic Acid, PAA) polyhexafluoropropylene, or styrene-butadiene rubber. The conductive agent is selected from, for example, any one or more selected from conductive carbon black, acetylene black, carbon nanotubes, and graphene. The thickener is selected from, for example, sodium carboxymethyl cellulose, etc.

[0043] In one embodiment of the present invention, the negative electrode current collector is selected from copper foil, for example, with a thickness of 8 μm to 16 μm, and the negative electrode active material, conductive agent, thickener and binder are mixed at a mass ratio of 95 to 98.9: 0.1 to 1: 1 to 2: 0 to 2, deionized water is added, and the negative electrode slurry is obtained by stirring. The negative electrode slurry is evenly coated on the copper foil, dried at room temperature, and then vacuum dried, cold pressed and cut to obtain the negative electrode sheet.

[0044] In one embodiment of the present invention, the electrolyte includes, for example, a non-aqueous solvent, a lithium salt, and an additive. The non-aqueous solvent is selected from any one or more of ethylene carbonate (EC), ethyl methyl carbonate (EMC), propylene carbonate (PC), ethyl acetate (EA), dimethyl carbonate (DMC), or diethyl carbonate (DEC). The lithium salt is selected from any one or more of lithium bis(fluorosulfonyl)imide (LiFSi), lithium difluorophosphate (LiPO2F2), lithium hexafluorophosphate (LiPF6), or lithium tetrafluoroborate (LiBF4). The additive is, for example, selected from any one or more of vinylene carbonate (VC), 1,3,2-Dioxathiolane 2,2-dioxide (DTD), fluoroethylene carbonate (FEC) or 1,3-propane sultone (PS). In one embodiment of the present invention, the lithium salt is, for example, selected from lithium hexafluorophosphate, and the non-aqueous solvent is, for example, selected from a mixture of ethylene carbonate and ethyl methyl carbonate. Ethylene carbonate and ethyl methyl carbonate are mixed in a mass ratio of 3:7, and in an argon atmosphere glove box with a water content of less than 10ppm, fully dried LiPF6 and additives are dissolved in the mixed non-aqueous solvent, and the electrolyte is obtained after uniform mixing, wherein the content of LiPF6 in the electrolyte is, for example, 6wt% to 15wt%, and the content of the additive in the electrolyte is, for example, 1wt% to 11wt%.

[0045] In one embodiment of the present invention, the diaphragm is, for example, a polyethylene film (PE), a polypropylene film (PP), a glass fiber film or a polyethylene film. And the thickness of the diaphragm is, for example, 9μm to 15μm. In one embodiment of the present invention, the above-mentioned positive electrode sheet, diaphragm, and negative electrode sheet are stacked in sequence, so that the diaphragm is located between the positive electrode sheet and the negative electrode sheet to play an isolating role. Then it is wrapped with an aluminum-plastic film, transferred to a vacuum oven and dried at 120°C, and the above-prepared electrolyte 3.0g / Ah is injected and then sealed, and the electrolyte is formed to finally prepare a soft-pack lithium-ion battery with a capacity of 1Ah.

[0046] Hereinafter, the present invention will be explained in more detail by citing examples, which should not be construed as limiting. Appropriate modifications may be made within the scope consistent with the gist of the present invention, all of which fall within the technical scope of the present invention.

[0047] Example 1

[0048] Preparation of positive electrode sheet: The positive electrode active material LiFePO4 and elemental boron are mixed by ball milling. In an argon atmosphere, equal amounts of 20mm and 15mm grinding balls are used, the ball-to-material ratio is 1:1, the ball milling time is 12h, and the ball milling speed is 500rpm / min to obtain a mixed active powder. The mixed active powder, the adhesive polyvinylidene fluoride and the conductive agent conductive carbon black are mixed in a mass ratio of 97:1:2. After the mixed active powder, the adhesive and the conductive agent are mixed evenly, the solvent N-methylpyrrolidone is added and stirred in a vacuum mixer until it is uniform and transparent to obtain a positive electrode slurry. The positive electrode slurry is evenly coated on a 9μm aluminum foil current collector, and then the current collector is dried at room temperature and transferred to a vacuum oven, dried at 120°C for 10h, and then cold pressed and cut to obtain a positive electrode sheet. In the positive active material layer, the content of elemental boron is 0.08wt%.

[0049] Preparation of negative electrode sheet: Mix the negative electrode active material artificial graphite, conductive agent conductive carbon black, thickener sodium carboxymethyl cellulose and binder styrene butadiene rubber in a mass ratio of 96:1:1:2, add deionized water, and obtain negative electrode slurry under the action of a vacuum mixer. The negative electrode slurry is evenly coated on a 9μm copper foil current collector, and the copper foil is dried at room temperature and transferred to a vacuum oven for drying, and then cold pressed and cut to obtain the negative electrode sheet.

[0050] Preparation of electrolyte: Battery-grade vinyl carbonate and ethyl methyl carbonate are mixed in a mass ratio of 3:7 to form a mixed solvent. In an argon atmosphere glove box with a water content of less than 10 ppm, fully dried LiPF6 is dissolved in the mixed solvent. Vinyl carbonate and vinyl sulfate are then added and mixed evenly to obtain an electrolyte, wherein the content of LiPF6 in the electrolyte is 12 wt%, the content of vinyl carbonate in the electrolyte is 2.5 wt%, and the content of vinyl sulfate in the electrolyte is 0.5 wt%.

[0051] Selection of diaphragm: Use 12μm thick polypropylene diaphragm.

[0052] Preparation of battery: The positive electrode sheet, separator and negative electrode sheet are stacked in sequence, and the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role. Then, the aluminum plastic film is wrapped outside, transferred to a vacuum oven for drying at 120°C, and the prepared electrolyte 3.0g / Ah is injected and sealed, and the electrolyte is formed, and finally a soft-pack lithium-ion battery with a capacity of 1Ah is prepared.

[0053] Example 2

[0054] In the positive electrode active material layer, the content of elemental boron is 1.5 wt %, and other operations are consistent with those in Example 1.

[0055] Example 3

[0056] In the positive electrode active material layer, the content of elemental boron is 2 wt %, and other operations are consistent with those in Example 1.

[0057] Example 4

[0058] In the positive electrode active material layer, the content of elemental boron is 0.5 wt %, and other operations are consistent with those in Example 1.

[0059] Example 5

[0060] The positive electrode active material LiFePO4 is mixed with elemental boron by reduction. The specific reduction steps include: mixing LiFePO4 into ice water containing ammonium fluoride, taking equal amounts of H3BO3 and LiBH4 according to the equivalent of elemental boron, dissolving H3BO3 first, stirring and mixing evenly, and then gradually adding LiBH4. After the addition is completed, react for 3 hours, filter, wash with deionized water, and calcine the material at 750°C in an oxygen environment for 1.5 hours.

[0061] In the positive electrode active material layer, the content of elemental boron is 0.08 wt %, and other operations are consistent with those in Example 1.

[0062] Example 6

[0063] The positive electrode active material LiFePO4 and elemental boron are mixed by reduction. In the positive electrode active material layer, the content of elemental boron is 0.5 wt %. Other operations are consistent with Example 1.

[0064] Example 7

[0065] The positive electrode active material LiFePO4 and elemental boron are mixed by reduction. In the positive electrode active material layer, the content of elemental boron is 1.5 wt %. Other operations are consistent with Example 1.

[0066] Example 8

[0067] The positive electrode active material LiFePO4 and elemental boron are mixed by reduction. In the positive electrode active material layer, the content of elemental boron is 2 wt %. Other operations are consistent with Example 1.

[0068] Example 9

[0069] Preparation of positive electrode sheet: LiFe 0.4 Mn 0.6 PO4 and elemental boron are mixed by ball milling. In an argon atmosphere, equal amounts of 20 mm and 15 mm grinding balls are used, the ball-to-material ratio is 1:1, the ball milling time is 12 h, and the ball milling speed is 500 rpm / min to obtain a blended active powder. The blended active powder, the adhesive polyvinylidene fluoride, and the conductive agent acetylene black are mixed in a mass ratio of 96:2:2. After the blended active powder, adhesive and conductive agent are evenly mixed, the solvent N-methylpyrrolidone is added and stirred in a vacuum mixer until it is uniform and transparent to obtain a positive electrode slurry. The positive electrode slurry is mixed at 0.3 g / 1540.25 mm 2 The coating amount is coated on both sides of the aluminum foil current collector with a thickness of 9 μm, and then dried, and then cold pressed and cut to obtain the positive electrode sheet. In the positive electrode active material layer, the content of single substance boron is 0.08wt%.

[0070] Preparation of negative electrode sheet: Mix the negative electrode active material artificial graphite, conductive agent conductive carbon black, thickener sodium carboxymethyl cellulose and binder styrene butadiene rubber in a mass ratio of 96:1:1:2, add deionized water, and obtain negative electrode slurry under the action of a vacuum mixer. The negative electrode slurry is evenly coated on a 9μm copper foil current collector, and the copper foil is dried at room temperature and transferred to a vacuum oven for drying, and then cold pressed and cut to obtain the negative electrode sheet.

[0071] Preparation of electrolyte: Battery-grade vinyl carbonate and ethyl methyl carbonate are mixed in a mass ratio of 3:7 to form a mixed solvent. In an argon atmosphere glove box with a water content of less than 10 ppm, fully dried LiPF6 is dissolved in the mixed solvent. Vinyl carbonate and vinyl sulfate are then added and mixed evenly to obtain an electrolyte, wherein the content of LiPF6 in the electrolyte is 12 wt%, the content of vinyl carbonate in the electrolyte is 2.5 wt%, and the content of vinyl sulfate in the electrolyte is 0.5 wt%.

[0072] Selection of diaphragm: Use 12μm thick polypropylene diaphragm.

[0073] Preparation of battery: The positive electrode sheet, separator and negative electrode sheet are stacked in sequence, and the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role. Then, the aluminum plastic film is wrapped outside, transferred to a vacuum oven for drying at 120°C, and the prepared electrolyte 3.0g / Ah is injected and sealed, and the electrolyte is formed, and finally a soft-pack lithium-ion battery with a capacity of 1Ah is prepared.

[0074] Example 10

[0075] In the positive electrode active material layer, the content of elemental boron is 0.5 wt %, and other operations are consistent with those in Example 9.

[0076] Embodiment 11

[0077] In the positive electrode active material layer, the content of elemental boron is 1.5 wt %, and other operations are consistent with those in Example 9.

[0078] Example 12

[0079] In the positive electrode active material layer, the content of elemental boron is 2 wt %, and other operations are consistent with those in Example 9.

[0080] Example 13

[0081] Preparation of positive electrode sheet: LiNi 0.93 Co 0.06 Mn 0.01O2 and elemental boron are mixed by ball milling. In an argon atmosphere, equal amounts of 20 mm and 15 mm grinding balls are used, the ball-to-material ratio is 1:1, the ball milling time is 12 h, and the ball milling speed is 500 rpm / min to obtain a blended active powder. The blended active powder, the adhesive polyvinylidene fluoride, and the conductive carbon black are mixed in a mass ratio of 98:1:1. After the blended active powder, the adhesive and the conductive agent are mixed evenly, the solvent N-methylpyrrolidone is added and stirred in a vacuum mixer until it is uniform and transparent to obtain a positive electrode slurry. The positive electrode slurry is evenly coated on a 9 μm aluminum foil current collector, and then the current collector is dried at room temperature and transferred to a vacuum oven, dried at 120 ° C for 10 h, and then cold pressed and cut to obtain a positive electrode sheet. In the positive electrode active material layer, the content of elemental boron is 0.5wt%.

[0082] Preparation of negative electrode: SiO x (x = 0.9-1.1) and artificial graphite in a mass ratio of 3:7 as the negative electrode active material, the negative electrode active material, the conductive agent carbon nanotubes and the binder polyacrylic acid in a mass ratio of 96:0.2:3.8 are mixed, deionized water is added, and the negative electrode slurry is obtained under the action of a vacuum mixer. The negative electrode slurry is evenly coated on a 9μm copper foil current collector, the copper foil is dried at room temperature and then transferred to a vacuum oven for drying, and then cold pressed and cut to obtain the negative electrode sheet.

[0083] Preparation of electrolyte: Battery-grade ethylene carbonate and ethyl methyl carbonate are mixed in a mass ratio of 3:7 to form a mixed solvent. In an argon atmosphere glove box with a water content of less than 10 ppm, fully dried LiPF6 is dissolved in the mixed solvent. Fluorinated ethylene carbonate and 1,3-propane sultone are added and mixed evenly to obtain an electrolyte, wherein the concentration of LiPF6 in the electrolyte is 6.25wt%, the content of fluoroethylene carbonate in the electrolyte is 10wt%, and the content of vinyl sulfate in the electrolyte is 0.5wt%.

[0084] Preparation of battery: The positive electrode sheet, separator and negative electrode sheet are stacked in sequence, and the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role. Then, the aluminum plastic film is wrapped outside, transferred to a vacuum oven for drying at 120°C, and the prepared electrolyte 3.0g / Ah is injected and sealed, and the electrolyte is formed, and finally a soft-pack lithium-ion battery with a capacity of 1Ah is prepared.

[0085] Comparative Example 1

[0086] The positive electrode active material is LiFePO4, and no elemental boron is added. The same ball milling process is performed on LiFePO4 and Example 1 to obtain a comparative sample made in the same batch. Other operations are consistent with Example 1.

[0087] Comparative Example 2

[0088] The positive electrode active material is LiFePO4, and no elemental boron is added. LiFePO4 is subjected to the same reduction operation as in Example 5, but no oxidant and reductant are added to obtain a comparative sample made in the same batch. Other operations are consistent with Example 5.

[0089] Comparative Example 3

[0090] The positive electrode active material is LiFe 0.4 Mn 0.6 PO4, without adding elemental boron, for LiFe 0.4 Mn 0.6 PO4 was ball milled, and other operations were consistent with Example 9.

[0091] Comparative Example 4

[0092] The positive electrode active material is LiNi 0.93 Co 0.06 Mn 0.01 O2, no elemental boron is added, and other operations are consistent with Example 13.

[0093] Lithium ion batteries were prepared using different positive electrode active materials in Examples 1-13 and Comparative Examples 1-4 of the present invention, and the rate performance of the lithium ion batteries was tested. The test results are shown in Tables 1 to 3.

[0094] In one embodiment of the present invention, in order to achieve the lithium supplementation effect of elemental boron, the lithium ion battery obtained in Examples 1-13 and Comparative Examples 1-4 is subjected to an activation charging step, the lithium ion battery is charged to 4.5V at a constant current of 1C, then charged at a constant voltage to a current less than 0.05C, left to stand for 30 minutes, and then discharged to a low voltage at 1C.

[0095] In one embodiment of the present invention, the high temperature cycle test is to perform cyclic charge and discharge in a specified potential range at a current of 1C in a 45°C oven after the activation charging step, and record the discharge capacity of each cycle. The test is terminated when the battery capacity reaches 80% of the first cycle capacity. The potential range of the lithium-ion battery with the positive electrode active material being LiFePO4 is 2.0V to 3.8V, and the positive electrode active material is LiFe 0.4 Mn 0.6 The potential range of PO4 lithium-ion battery is 2.5V~4.2V, and the positive electrode active material is LiNi 0.93 Co 0.06 Mn 0.01 The potential range of O2 lithium-ion batteries is 2.8V to 4.2V.

[0096] In one embodiment of the present invention, the gas production volume change rate test is to charge the lithium-ion battery cell to 100% state of charge (SOC) before starting the high-temperature cycle, and then measure the cell volume V1 by the water discharge method. After the high-temperature cycle is completed, the cell is fully charged again, and the cell volume V2 is measured by the water discharge method, and the cycle gas production is obtained by: (V2-V1) / V1×100%.

[0097] In one embodiment of the present invention, corresponding to the high nickel system, the 250-cycle capacity recovery test is performed by charging with an upper limit voltage of 4.5V every 250 cycles.

[0098] The present invention selects some embodiments and comparative examples to study the effects of the combination of positive electrode active material LFP and lithium supplement agent elemental boron on the performance of lithium-ion batteries. The results are shown in Table 1.

[0099] Table 1. Performance test results of lithium ion batteries in Examples 1-8 and Comparative Examples 1-2

[0100]

[0101] Please refer to Table 1. In combination with Examples 1-8 and Comparative Examples 1-2, adding elemental boron as a lithium supplement to the positive electrode active material can increase the number of cycles of the lithium-ion battery. And as the content of elemental boron increases, the number of cycles is significantly improved, while the gas production problem of the lithium-ion battery is slightly improved, and the gas production of the lithium-ion battery is not worsened. Due to the poor conductivity of elemental boron, in the positive electrode active material layer, it is doped up to 2wt% according to the process requirements to ensure the energy density of the lithium-ion battery. In combination with Examples 1-8, in the method of doping elemental boron into the positive electrode active material, the effect trends of the ball milling method and the reduction method are similar. In the same chemical system, the same amount of elemental boron added, the cycle performance of the lithium-ion battery doped with elemental boron prepared by the reduction method is better. This is because the conductivity of elemental boron is extremely poor. Therefore, the contact between the introduced elemental boron and the conductive material in the positive electrode sheet determines the capacity of the elemental boron. The better the contact effect, the greater the capacity. In the reduction method, elemental boron is generated in situ on the surface of the positive electrode active material. It has a closer contact with the positive electrode active material, so it is easier to exert its capacity than the ball milling method. Therefore, it is better for improving the performance of lithium-ion batteries.

[0102] The present invention selects some embodiments and comparative examples to study the effect of the combination of positive electrode active material LMFP and lithium supplement agent elemental boron on the performance of lithium ion batteries. The results are shown in Table 2.

[0103] Table 2 Performance test results of lithium ion batteries in Examples 9-12 and Comparative Example 3

[0104]

[0105] As shown in Table 2, in combination with Examples 9-12 and Comparative Example 3, in the system where the positive electrode active material is LMFP, adding elemental boron as a lithium supplement can increase the number of cycles of the lithium-ion battery. And as the content of elemental boron increases, the number of cycles is significantly improved, while the gas production of the lithium-ion battery is not deteriorated, solving the problem that conventional lithium supplement materials deteriorate the gas production of LMFP in the LMFP system, and being able to achieve improved cycle performance without deteriorating the gas production of LMFP.

[0106] The present invention selects some embodiments and comparative examples to study the effect of using the positive electrode active material NCM and the lithium supplement elemental boron on the performance of lithium-ion batteries. The results are shown in Table 3.

[0107] Table 3 Performance test results of lithium ion batteries in Example 13 and Comparative Example 4

[0108]

[0109] Please refer to Table 3. In combination with Example 13 and Comparative Example 4, for the high-nickel and high-silicon system, the conventional cycle step is to charge to 4.25V. At this time, the elemental boron will not be oxidized, and therefore will not contribute to the capacity. The positive electrode capacity is entirely contributed by the delithiation of the positive electrode active material. In the cycle of the high-nickel and high-silicon battery, the negative electrode will produce serious active lithium loss, that is, the lithium ions embedded in the negative electrode cannot return to the system during the discharge process. At the same time, the negative electrode has a margin and can continue to embed lithium. In Example 13 and Comparative Example 4, the lithium-ion battery is charged at 4.5V every 250 cycles to oxidize the elemental boron in the positive electrode, force the negative electrode to embed lithium to fill the capacity, and achieve lithium replenishment. Thereby, capacity recovery can be effectively achieved, and ultra-long cycles can be achieved compared to Comparative Example 4.

[0110] The present invention also provides an electronic device, the electronic device includes at least one of the above-mentioned lithium-ion batteries, and the lithium-ion battery is used to provide electrical energy. Among them, the electronic device can be a vehicle, a mobile phone, a portable device, a laptop computer, a ship, a spacecraft, an electric toy and an electric tool, etc. In one embodiment of the present invention, the vehicle is, for example, a new energy vehicle, and the new energy vehicle can be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. Spacecraft include airplanes, rockets, space shuttles and spacecrafts, etc. Electric toys include fixed or mobile electric toys, such as game consoles, electric car toys, electric ship toys and electric airplane toys, etc. Electric tools include metal cutting electric tools, grinding electric tools, assembly electric tools and railway electric tools, such as electric drills, electric grinders, electric wrenches, electric screwdrivers, electric hammers, impact drills, concrete vibrators and electric planers, etc. The electronic device includes the above-mentioned lithium-ion battery, so the advantages of the above-mentioned lithium-ion battery are included, which will not be elaborated here.

[0111] In summary, the present invention proposes a lithium ion battery and its preparation method and application. By selecting elemental boron as a positive electrode lithium supplement, during charging, an oxidation reaction occurs to contribute a large number of charges, and after oxidation, it will be positively charged, which can form a charge balance with the lithium ions embedded in the negative electrode, and will not cause the solution ion charge to be non-conserved because it does not contribute lithium ions, and can achieve the lithium supplement effect. At the same time, elemental boron has a large specific capacity and a strong ability to fill the irreversible capacity of the negative electrode, which can play a high positive electrode lithium supplement effect. The product after oxidation of the lithium supplement can improve the film quality of the positive electrode electrolyte interface film and reduce the DC impedance. Through the reduction method, elemental boron is in situ generated on the surface of the positive electrode active material, and its contact with the positive electrode active material is closer. Compared with the ball milling method, it is easier to exert the capacity, and the performance improvement of the lithium ion battery is better. When elemental boron is used as a positive electrode lithium supplement, it can be applied to a variety of battery systems, and can improve the cycle performance of lithium ion batteries without deteriorating gas production.

[0112] The above description is only a preferred embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of the invention involved in the present application is not limited to the technical solution formed by a specific combination of the above-mentioned technical features, but should also cover other technical solutions formed by any combination of the above-mentioned technical features or their equivalent features without departing from the inventive concept, such as a technical solution formed by replacing the above-mentioned features with (but not limited to) technical features with similar functions disclosed in this application.

[0113] Except for the technical features described in the specification, the remaining technical features are known technologies to those skilled in the art. In order to highlight the innovative features of the present invention, the remaining technical features will not be described here in detail.

Claims

1. A lithium ion battery, characterized in that: At least: A positive electrode plate, wherein the positive electrode plate includes a lithium supplement, and the lithium supplement includes elemental boron; Negative electrode; A separator, disposed between the positive electrode sheet and the negative electrode sheet; and The electrolyte is filled between the positive electrode sheet, the negative electrode sheet and the separator.

2. The lithium-ion battery according to claim 1, characterized in that The positive electrode plate includes a positive electrode current collector and a positive electrode active material layer at least arranged on one side of the positive electrode current collector, and the content of the lithium supplement in the positive electrode active material layer is 0.08wt% to 2wt%.

3. The lithium-ion battery according to claim 2, characterized in that: The positive electrode active material layer includes a positive electrode active material, and the positive electrode active material is selected from at least one of lithium iron phosphate and lithium manganese iron phosphate.

4. The lithium-ion battery according to claim 2, characterized in that: The positive electrode active material layer includes a positive electrode active material, and the positive electrode active material is selected from LiNi x Co y Mn 1-x-y O2, where 0.65≤x<1.0, 0≤y<0.

5.

5. The lithium-ion battery according to claim 1, characterized in that: The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed at least on one side of the negative electrode current collector. The negative electrode active material layer includes a negative electrode active material, and the negative electrode active material is selected from at least one of graphite, silicon-oxygen material or silicon-carbon material.

6. A method for preparing a lithium ion battery, characterized in that: At least the following steps are included: Mixing a lithium supplement agent into the positive electrode active material to obtain a mixed active powder; The mixed active powder is prepared into positive electrode slurry; The positive electrode slurry is coated on the positive electrode current collector, and then dried and cold pressed to obtain a positive electrode sheet; preparing negative electrode active materials into negative electrode slurry; The negative electrode slurry is coated on the surface of the negative electrode current collector, and then dried and cold pressed to obtain a negative electrode sheet; and The lithium-ion battery is obtained by assembling the positive electrode sheet, the negative electrode sheet, the electrolyte and the separator.

7. The method for preparing a lithium ion battery according to claim 6, characterized in that: The lithium supplement agent and the positive electrode active material are uniformly mixed by ball milling.

8. The method for preparing a lithium ion battery according to claim 7, characterized in that: The powder particle size of the lithium supplement agent is 10nm to 500nm.

9. The method for preparing a lithium ion battery according to claim 6, characterized in that: The blended active powder is obtained by the following method: Add the positive electrode active material to the ice water or ice N,N-dimethylacetamide solvent containing ammonium fluoride, first dissolve the boric acid according to the amount of the lithium supplement, stir and mix evenly, then gradually add dimethylamine borane or lithium borohydride dropwise; After the dropwise addition is completed, the mixture is reacted for a first preset time, filtered and washed to obtain an intermediate product; The intermediate product is calcined at a preset temperature and oxygen environment for a second preset time.

10. An electronic device, characterized in that: A lithium-ion battery comprising any one of claims 1 to 5.

Citation Information

Patent Citations

  • Lithium ion battery and anode lithium supplementing method thereof

    CN114583296A

  • Positive electrode lithium supplement agent and preparation method thereof, positive electrode plate, lithium ion battery and electric device

    CN118572053A

  • Lithium secondary battery

    JP1994267538A

  • Structure damage evaluation method for using the convolutional neural network, and computing apparatus for performing the method

    KR102494829B1

Cited By

  • Repair method and application of degenerated electrode of lithium iron phosphate battery

    CN119905692A

  • A method for repairing degraded electrodes of lithium iron phosphate batteries and applications thereof

    CN119905692B